Association between Physical Characteristics and Locomotive Syndrome in Elderly in Surabaya, Indonesia - Benni Azhari; Imam Subadi; Patricia Maria Kurniawati (Institute of Medico-legal Publications Pvt Ltd, 2021)
The locomotive syndrome (LS) is a condition of reduced mobility due to impairment of locomotive organ. The LS was screened by Lococheck in elderly population. Prior research has been shown that physical characteristic such as age, gender, body weight, body height and body mass index has correlation with mobility limitation in elderly. We aimed to asses if the physical characteristic in elderly is able to use as a screening tool for locomotive syndrome in Indonesia. To investigate the association between physical characteristic and locomotive syndrome in elderly. This study was an observational cross-sectional study. A total 63 participants (37 females and 27 males) age 60-78 years participated in this study. This study was conducted by filling the Lococheck Indonesian version and measuring physical characteristic (Age, gender, body weight, body height and body mass index). The correlation between the Lococheck Indonesian version with physical characteristic was analyzed using Kendall’s tau correlation test. Forty participant answer “yes” at least one item of the lococheck Indonesian version questionnaire. The lococheck result showed an insignificant correlation with age r<0.3 (0.01), p>0.05 (0.926), gender r<0.3 (0.061), p>0.05 (0.563), Body weight r<0.3 (0.061), p>0.05 (0.562), body height r<0.3 (-0.104), p>0.05 (0.328) and body mass index r<0.3 (0.122), p>0.05 (0.245). To sum up, these findings confirmed that no correlation between physical characteristic and locomotive syndrome in elderly